Meta-ethnography in healthcare research: a guide to using a meta-ethnographic approach for literature synthesis - Sattar, Raabia; Lawton, Rebecca; Panagioti, Maria; Johnson, Judith (BMC health services research, 2021)
Background Qualitative synthesis approaches are increasingly used in healthcare research. One of the most commonly utilised approaches is meta-ethnography. This is a systematic approach which synthesises data from multiple studies to enable new insights into patients’ and healthcare professionals’ experiences and perspectives. Meta-ethnographies can provide important theoretical and conceptual contributions and generate evidence for healthcare practice and policy. However, there is currently a lack of clarity and guidance surrounding the data synthesis stages and process. Method This paper aimed to outline a step-by-step method for conducting a meta-ethnography with illustrative examples. Results A practical step-by-step guide for conducting meta-ethnography based on the original seven steps as developed by Noblit & Hare (Meta-ethnography: Synthesizing qualitative studies.,1998) is presented. The stages include getting started, deciding what is relevant to the initial interest, reading the studies, determining how the studies are related, translating the studies into one another, synthesising the translations and expressing the synthesis. We have incorporated adaptations and developments from recent publications. Annotations based on a previous meta-ethnography are provided. These are particularly detailed for stages 4–6, as these are often described as being the most challenging to conduct, but with the most limited amount of guidance available. Conclusion Meta-ethnographic synthesis is an important and increasingly used tool in healthcare research, which can be used to inform policy and practice. The guide presented clarifies how the stages and processes involved in conducting a meta-synthesis can be operationalised.